2021
DOI: 10.1186/s12889-021-11248-z
|View full text |Cite|
|
Sign up to set email alerts
|

Supporting parents and healthy behaviours through parent-child meetings – a qualitative study in the Netherlands

Abstract: Background The first 2 years of a child’s life have been found to be crucial to healthy growth and development. Parent support groups can help parents to promote health-related behaviours during this crucial period. The aim of this study was to explore the experiences of parents who participated in a parent support group (Parent-Child Meetings) which promoted health-related behaviours of their children, and to determine whether and how these meetings supported them in promoting these behaviours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…A phenomenological study was carried out to describe the trajectory of older adults seeking community care [ 36 ]. We employed participatory observations and in-depth interviews with older adults in two communities in Guangzhou, Guangdong, China [ 37 , 38 ]. The Consolidated Criteria for Reporting Qualitative study (COREQ) checklist was followed.…”
Section: Methodsmentioning
confidence: 99%
“…A phenomenological study was carried out to describe the trajectory of older adults seeking community care [ 36 ]. We employed participatory observations and in-depth interviews with older adults in two communities in Guangzhou, Guangdong, China [ 37 , 38 ]. The Consolidated Criteria for Reporting Qualitative study (COREQ) checklist was followed.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that whole-of-community interventions are more effective for people with lower than higher SEP backgrounds ( 60 ). Parent support groups are appreciated by parents of young children and seem to contribute to enhancing parental knowledge, skills and practices regarding healthy behaviors, potentially benefitting young children's health behaviors ( 61 ). Moreover, a systematic review also supports the idea that interventions involving more active parental engagement strategies, such as social support, are more effective in the prevention of early childhood obesity ( 62 ).…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 99%
“…Such family caregivers are the main cornerstone of care, directly dealing with the health centers, social, and community services, so that their awareness as well as their attitudes and practices toward the ESRD children influence their quality of care and their QOL (Al-agamy et al, 2022). Bektas et al (2021) have demonstrated that the majority of families are capable of successfully coping with their children's chronic illnesses. On the other side, some of them might also have trouble adapting to it.…”
Section: Introductionmentioning
confidence: 99%